Low cost environmentally friendly ultrasonic embossed electronic circuit board - Gielen, Paul; Sillen, Rob; Puik, Erik (2012 4th Electronic System-Integration Technology Conference, 2012)
In this paper the focus is on a new alternative production process for a printed circuit board (PCB). Most microproducts have electronic functions that are integrated on a PCB. Additionally these products need to be fitted in a housing. It's investigated whether the PCB can be integrated with the housing in a cost effective way. The process is designed in such way that it can be implemented on an open manufacturing concept for micro fabrication, micro assembly and micro packaging; the concept of 'Equiplet Manufacturing'. If it appears possible to combine the housing material and the functionality of a PCB, the traditional PCB creation process can be skipped which is a major step towards an Environmental Friendlier Production Process (EFPP). The investigations for creation of a pattern in the encapsulating plastic by using ultrasonic embossing are described. As a result of this integration, a production process has been developed that is flexible, fast, low cost, according to EFPP and may be categorized as 'Agile'. Ultrasonic embossing was realized with an industry standard ultrasonic welder. The moulds were created by micro milling the electronic patterns into a brass substrate; this is a known process, which enables sufficient flexibility. In state of the art systems, the hot embossing process requires the total machine to be in a vacuum environment. In this concept however, a local vacuum is created only around the mould in the ultrasonic welder. With the plastic substrate on top of the mould, a 'vacuum chamber' is created. By heating the substrate with the welder, an embossed replica of the pattern could successfully be created. The embossing process was tested with several materials; PET(G), PS & PP. The embossing parameters, like ultrasonic power, pressure (force) and the process-time have been scanned and tuned. The results of the ultrasonic embossing process were promising from an industrial point of view; no enclosures of air bubbles were seen and the products replicated in a uniform way. Some replicated parts were 'raked' with solder paste and conductive adhesive to show the quality of the imprints. The electromechanical parameters of the raked conductors and the dimensions of the electronic paths in the pattern were decisive for the quality and the electronic functionality. The investigations on the conducting paste have not been completed yet and are subject to continued research. The main goal of creating functional electronic circuits in a minimal amount of process steps, by placing the components on the created conducting lines before curing, still seams realistic.